2023
DOI: 10.1007/s10459-023-10231-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mindfulness-based interventions in medical students: a systematic review

Ilona Kaisti,
Petri Kulmala,
Mirka Hintsanen
et al.

Abstract: The number of studies on the effects of mindfulness on healthcare professionals is increasing. The main aim of this study was to collate the quantitative results of original studies analyzing the effects of mindfulness-based interventions on a variety of outcomes in medical students. We also analyzed how the study design and characteristics of the intervention affect the results, and identified qualitative effects of mindfulness interventions. A literature search was performed in different databases in June 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In fact, other studies on the same target population, namely young adults, have mostly investigated mindfulness-based interventions that gave priority to the mindfulness practices. Systematic reviews of studies evaluating mindfulness-based interventions in university students have shown improvements in respect to stress and mindfulness ( 81–83 ) , mental health and well-being ( 81–83 ) but also coping capacities ( 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, other studies on the same target population, namely young adults, have mostly investigated mindfulness-based interventions that gave priority to the mindfulness practices. Systematic reviews of studies evaluating mindfulness-based interventions in university students have shown improvements in respect to stress and mindfulness ( 81–83 ) , mental health and well-being ( 81–83 ) but also coping capacities ( 82 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that MBIs effectively contribute to the reduction of stress levels; although there are still numerous unknowns regarding the mechanisms underlying MBIs. Studies suggested that they could foster cognitive flexibility, disrupt rumination on past events and future worries, enhance self-awareness for early recognition of stress, improve stress management skills and facilitate behavioural regulation (Kaisti et al, 2023). The relevant neurobiological mechanisms suggest that stress induces a reduction in the quantity of glucocorticoid receptors (GR) within the hippocampus, as well as activation of the hypothalamic-pituitary-adrenal (HPA) axis, which initiates the release of glucocorticoids (GC); however, prolonged exposure to elevated levels of GC stimulation in the hippocampus leads to an intensified state of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness stress reduction training combines meditation, yoga and other activities, and applies psychological intervention and guidance to achieve the purpose of improving the emotional state of patients[ 7 , 17 , 18 ]. The training node is calculated by week, guiding patients to do mindfulness training step by step every week, and ensuring that the content of the previous week is reviewed and analyzed before each training, which can effectively divert their attention[ 19 , 20 ]. Here, we found that compared with the control group, the recovery time of bowel sound, ventosity and abdominal pain improvement time, venting time and cacation time of patients in the observation group were shorter, and the total incidence of complications was reduced.…”
Section: Discussionmentioning
confidence: 99%